Impairment in circadian activity rhythms occurs during dexamethasone therapy in children with leukemia. Issue 11 (25th July 2014) - Rogers, Valerie E.; Zhu, Shijun; Ancoli‐Israel, Sonia; Hinds, Pamela S.
<x xml:space="preserve">Abstract</x> Background Circadian rhythm disturbances in adults with cancer are associated with fatigue, time to relapse, and death. This study of circadian activity rhythms (CAR) of children with acute lymphoblastic leukemia (ALL) on continuation chemotherapy aimed to describe CAR before and after starting dexamethasone, and to determine whether fatigue was associated with less robust CAR. Procedure This was a secondary analysis of data from a multi‐institutional study in which children with ALL aged 5–18 years wore an actigraph for 10 consecutive 24‐hour periods, five before and five during dexamethasone therapy. CAR parameters measured by actigraphy were calculated for each 5‐day period, including peak activity, MESOR, amplitude, acrophase, and circadian quotient. Fatigue was measured on study days 2, 5, 7, and 10 by parent‐report and self‐report for children ≥7 years. Results Eighty‐two children qualified for CAR analysis, and 87 for analysis of daily peak activity patterns and fatigue. Mean age was 8.8 ± 3.3 years. Peak activity, MESOR, and amplitude significantly decreased during dexamethasone therapy. Children on high‐dose dexamethasone (8 or 12 mg/m2/d) had significantly higher (better, or more robust) values of several CAR parameters than those on low‐dose (6 mg/m2/d). There was a significant trend of decreasing daily pattern of peak activity during dexamethasone therapy only. Fatigue increased across the study and was associated with decreasing CAR peak activity, MESOR, and amplitude. Conclusions Dexamethasone initiation was associated with a decrease in several CAR parameters, and a significant decrease in the trend of daily peak activity. Fatigue was associated with less robust CAR. Pediatr Blood Cancer 2014;61:1986–1991. © 2014 Wiley Periodicals, Inc.